2007
DOI: 10.1016/j.socscimed.2007.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Who kicks the habit and how they do it: Socioeconomic differences across methods of quitting smoking in the USA

Abstract: Although the prevalence of smoking has declined among U.S. adults, an estimated 22.5 percent of the adult population (45.8 million adults) regularly smoked in 2002. Starting from this level, it will not be possible to achieve the Healthy People national health objectives of a reduction in the prevalence of smoking among adults to less than 12 percent by 2010 unless the rate of smoking cessation substantially rises from its current average of about 2.5 percent per year. To achieve that goal it is imperative tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…Other possible explanations for a lack of significant findings include: (1) our analyses utilised GRPs versus TRPs measuring exposure for young adults and (2) the possibility that young adults are less likely than older adults to make use of pharmaceutical methods of quitting and thus advertising levels are not as salient. Support for this hypothesis is suggested by some Canadian and US studies 41 42. Prior research examining the comparative effects of tobacco control policies and televised anti-smoking advertising with a large Australian adult sample found that smoking prevalence was not related to pharmaceutical advertising levels or sales of nicotine replacement therapy or other pharmaceutical products 8…”
Section: Discussionmentioning
confidence: 98%
“…Other possible explanations for a lack of significant findings include: (1) our analyses utilised GRPs versus TRPs measuring exposure for young adults and (2) the possibility that young adults are less likely than older adults to make use of pharmaceutical methods of quitting and thus advertising levels are not as salient. Support for this hypothesis is suggested by some Canadian and US studies 41 42. Prior research examining the comparative effects of tobacco control policies and televised anti-smoking advertising with a large Australian adult sample found that smoking prevalence was not related to pharmaceutical advertising levels or sales of nicotine replacement therapy or other pharmaceutical products 8…”
Section: Discussionmentioning
confidence: 98%
“…Our sample clearly shows both same-sex and different-sex cohabiters have lower rates of health insurance, while cohabiters—especially different-sex cohabiters—suffer relatively high rates of poverty and unemployment compared to the different-sex married. Rates of poverty, employment status, and health insurance may promote cohabiters’ greater current smoking risk relative to their different-sex married counterparts with more advantaged SES because these factors are associated with increased self-efficacy (Mirowsky and Ross 2007), access to smoking cessation programs (Cokkinides et al 2005; Fagan et al 2007a; Lillard et al 2007), and workplaces and health insurance initiatives that reduce smoking acceptability and availability (Bauer et al 2005). Notably, these SES factors do not reduce the risk of being a former smoker—an unexpected finding given the particular importance of access to nicotine dependence and smoking cessation programs that are associated with these SES factors (Manley et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This is due in part to smoking restrictions, clear air rules, non-smoking norms, and insurance initiatives at full-time higher-income workplaces that reduce the availability and acceptability of smoking (Bauer et al 2005; Sorensen et al 2004). Moreover, individuals with higher income, who have health insurance, and/or are employed full-time have an increased sense of self-efficacy and personal control (Mirowsky and Ross 2007) and are able to afford and access more effective nicotine cessation programs (Cokkinides et al 2005; Fagan et al 2007a, b; Lillard et al 2007; Manley et al 2003); these factors deter smoking initiation, reduce smoking dependence, and promote smoking cessation. Additionally, low income and poverty, lack of health insurance, and un/under-employment are each related to increased stress (Arnetz et al 2010; Finkelstein et al 2012), in part because SES advantaged individuals are more likely to participate in stress-reducing activities (e.g., counseling services, physical activity) (Baker et al 2004; Biddle and Mutrie 2008; Wang et al 2005).…”
Section: Union Status and Smokingmentioning
confidence: 99%
“…[19] However, studies on the association between education attainment and use of smoking-cessation services showed mixed results. Some studies found no association between socioeconomic status (SES) and use of cessation services, [18][19][20] one study found less-educated smokers are more likely to use cessation program than more-educated smokers among those who successfully quitted, [21] and one study found no consistent SES pattern in use of different kinds of cessation services. [22] In 2002, the Taiwan government launched a nationwide Outpatient Smoking Cessation Services (OSCS) program, aiming to increase successful smoking cessation among adults aged 19 or older.…”
Section: Introductionmentioning
confidence: 99%